Role of Promotion in Creating Influence Power, Impulsive Buying, and Autographical Memory - Haryanto, Jony Oktavian (SBM ITB, 2009)
Children are unique and also potential market They are unique, because they usually do not spend their own money but they have huge purchasing power. They are potential, because from the number of kids and spending, they are big and promising. Kids market consists of three markets, they are: First, primary markets which is targeting the children itself. Second, influence market which is emphasizing the influence that children assert on family purchases. Third, future market which is considering the future market from the children. Based on the huge market of the children, the author wants to identify the role of promotion as an antecedent of intention to consume for children and its impact on influence power, impulsive buying, and autobiographical memory. Furthermore, it is needed to identify the antecedent of autobiographical memory for children.Keywords: promotion, impulsive buying, autobiographical memory